Impact of livelihood skills training programme on youth development in Wedza district. - Biza, Rutendo (Midlands State University, 2018)
Livelihood skills training programs have become very important in reducing lack of skills and unemployment in the globe. The youths in Zimbabwe constitute a greater proportion of the total population and the rural youths are the most marginalized in issues to do with obtaining skills that are necessary for them to improve their livelihood. The government has introduced various programs to make sure that youths attain necessary skills but it has rather neglected the rural youths. This has called in for various organisations to come and fill in the loophole as done by Restless Development in making sure that the rural youths also acquire the relevant skills as their urban counterparts. The study is an investigation of Wedza district where youths in various wards have attained skills trainings and the researcher will examine the extent to which the skills have had an impact towards youth development. The research used a quantitative research method. Data were collected using structured questionnaires only and analyzed using SPSS analytical software. The results of the study indicated that the skills trainings had positive impact towards youths’ development as the youths have managed to create self -employment through the use of skills obtained. In light of the findings, the government of Zimbabwe and particularly the Ministry of Youth, Indigenization and Economic Empowerment is advised to implement the program in all rural societies of Zimbabwe as a way of capacitating the rural youths with relevant skills that will enable them to curb unemployment.